2007
DOI: 10.1111/j.1745-7254.2007.00675.x
|View full text |Cite
|
Sign up to set email alerts
|

AICAR inhibits proliferation and induced S-phase arrest, and promotes apoptosis in CaSki cells

Abstract: Aim: The aim of the present study was to determine the effect of 5‐aminoimidazole‐4‐carboxamide‐ribonucleoside (AICAR) on proliferation, cell cycle, and apoptosis in the human epithelial cervical cancer cell line CaSki cells. Methods: Cell count and 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide assay were used to determine cell proliferation and viability. Hoechst 33258 staining was conducted to distinguish the apoptotic cells. Cell cycle and Annexin‐V/propidium iodide staining were analyzed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…In other cancer cells (e.g. CaSki cells), AICAR significantly decreases G1 and G2 phase populations, but the proportion of cells in S-phase rises (Guan et al 2007). In line with the findings of the cited report, we found that AICAR treatment increased the S-phase population in BRAF-mutant thyroid cancer cells, compared with wild-type cells, after 48 h of incubation with AICAR (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In other cancer cells (e.g. CaSki cells), AICAR significantly decreases G1 and G2 phase populations, but the proportion of cells in S-phase rises (Guan et al 2007). In line with the findings of the cited report, we found that AICAR treatment increased the S-phase population in BRAF-mutant thyroid cancer cells, compared with wild-type cells, after 48 h of incubation with AICAR (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…AMPK regulates metabolic processes, including fatty acid synthesis, glucose uptake, and biogenesis of glucose transporter 4 (Bergeron et al 1999, Winder 2001, Ojuka 2004. AMPK activation has been implicated in regulation of cell proliferation and cell cycle progression and AMPK is considered to be potential target in cancer therapy (Luo et al 2005, Guan et al 2007, Fogarty & Hardie 2010. 5-Aminoimidazole-4-carboxamide-ribonucleoside (AICAR), a cell-permeable nucleoside used as an AMPK activator, has pro-apoptotic effects in cancer cell lines (Meisse et al 2002, Kefas et al 2003, Dagon et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…(16) Agents such as the AMP-mimetic 5-aminoimidazole-4-carboxamide ribonucleoside (AICAR) have been shown to activate AMPK by energy starvation leading to phosphorylation of TSC2 at Thr-1277 and Ser-1345. (13,17) Phosphorylation at these sites increases the activity of the TSC1-TSC2 complex to inhibit mTOR. (12,18).…”
Section: Discussionmentioning
confidence: 99%
“…AICAR plays a central role in the metabolism and in signal transduction increasing insulin properties, up-regulating mitochondrial enzymes in muscles and decreasing intra-abdominal fat [2][3][4] . It can act as an agonist and antagonist for a number of enzymes crucial for the cell life; among these, AMPKa has a fundamental role in energy homeostasis, being an energy sensor implicated in various 24,25 . Interestingly, in terms of cell proliferation, we have tested ERK1/2 phosphorylation: according to the MTT results, at 2 h of incubation, ERK1/2 phosphorylation was down regulated in treated cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%